2022
DOI: 10.1002/chem.202200609
|View full text |Cite
|
Sign up to set email alerts
|

Luminescent Organic‐Inorganic Hybrid Metal Halides: An Emerging Class of Stimuli‐Responsive Materials

Abstract: Luminescent organic-inorganic metal halides (OIMHs) are well known as a new materials family in recent years. Novel materials and applications of luminescent OIMHs have been explored by changing either the organic component or the metal halide species. Thereinto, the stimuliresponsive (SR) phenomena in OIMHs have drawn much attention recently, for not only their attractive application potential but also the helpfulness in understanding the stability of OIMHs to the external environment. Herein, the luminescent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 78 publications
3
17
0
Order By: Relevance
“…After analyzing the steady-state and time-resolved PL spectra of the title compound, the PL mechanism is proposed as shown in Figure 2 d [ 40 ]. Under excitation, the electrons in ground state 1 S 0 orbitals are excited to the singlet excited state 1 P 1 and triplet excited state 3 P n orbitals.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…After analyzing the steady-state and time-resolved PL spectra of the title compound, the PL mechanism is proposed as shown in Figure 2 d [ 40 ]. Under excitation, the electrons in ground state 1 S 0 orbitals are excited to the singlet excited state 1 P 1 and triplet excited state 3 P n orbitals.…”
Section: Resultsmentioning
confidence: 99%
“…Since the water molecule is always present in environments, such as the atmosphere, the water-molecule-sensing is of vital importance for meteorology, industrial production and human health [ 35 , 36 , 37 , 38 ]. Today’s sensors for humidity detection include fiber optic [ 39 ], fluorescence [ 40 ], quartz crystal microbalance (QCM) [ 41 ], and capacitive and resistive ones [ 42 ]. Optical-based humidity sensors usually have better sensitivity and can be used in environments with strong electromagnetic interference [ 43 ].…”
Section: Introductionmentioning
confidence: 99%
“…Due to the potential application of pressure-induced emission (PIE) in pressure sensing, great progress has been made in the development of materials with PIE in the past decade. 124 Meanwhile, research on the relationship between pressure and the luminescence characteristics of metal halide perovskites has also attracted extensive attention. 125–130 PIE phenomena have been found in various low-dimension OIHPs including C 4 N 2 H 14 SnBr 4 , C 4 N 2 H 14 PbBr 4 , and (BA) 4 AgBiBr 8 (BACH 3 (CH 2 ) 3 NH 3 + ), etc .…”
Section: Regulation Strategy Of White Emission From Oihpsmentioning
confidence: 99%
“…15 At the same time, it also shows that the electronic coupling interaction between [InCl 6 ] 3− anions is weak, which can inhibit non-radiative energy transfer and promote radiative recombination. 44,45 To explore the thermal stability of single crystals, we performed thermogravimetric analysis (TGA) and found that the mass loss of (DETA)InCl 6 occurred at 213 °C (Fig. S2 †), showing that the compound has great thermal stability below 200 °C.…”
Section: Crystal Structures and Supramolecular Interactionsmentioning
confidence: 99%